Increasing Financial Inclusion of Generation Z Through Digital Literacy, Lifestyle, and Qris Mediated Path Analysis - Indriana; Muhammad Yusuf; Lina Mariana; Asryanti; Nur Sandi Marsuni; Ismawati (Universitas Muhammadiyah Malang, 2026)
Purpose: This research aims to examine the role of digital literacy and lifestyle in strengthening financial inclusion among Generation Z, with the usage of the Quick Response Code Indonesian Standard (QRIS) as a mediating variable. Methodology/approach: This study employs a quantitative approach using a cross-sectional survey design. Data were composed from students of faculties of economics and business at several universities in South Sulawesi using purposive sampling techniques. Path analysis was applied to analyze the relationships among digital literacy, lifestyle, QRIS usage, and financial inclusion. Findings: The discoveries present that digital literacy and lifestyle have a significant influence on QRIS usage. Furthermore, QRIS usage plays a mediating role in strengthening the correlation between digital literacy, lifestyle, and financial inclusion among Generation Z. Practical implications: The outcomes give practical insights for policymakers, financial institutions, and educational institutions in constructing strategies to strengthen financial inclusion through digital payment systems targeting Generation Z. Originality/value: This study offers empirical evidence on the mediating part of QRIS in financial inclusion, an area that remains underexplored in the context of Generation Z in Indonesia.